2007
DOI: 10.1016/j.cellbi.2006.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of human bone marrow‐derived mesenchymal stem cells passaged in vitro

Abstract: This study concerns the cytogenetic stability of in vitro human bone marrow-derived mesenchymal stem cells (MSCs) in primary culture and after passaging. Bone marrow samples were collected from seven brain malfunction patients involved in autologous MSC transplantation trials. Chromosome preparations from primary MSC cultures and after 3 passages were analyzed by conventional staining and G-banding techniques. All MSCs showed normal diploid karyotypes, 46 XY or 46 XX, without aneuploidy or polyploidy; chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 10 publications
6
58
0
4
Order By: Relevance
“…The age of the donors included in our study ranged from 21-86 years. These observations are in agreement with data from other investigators, [21][22][23]34,35 who reported normal diploid karyotype without aneuploidy or polyploidy in MSCs from healthy donors or patients with no hematopoietic disorders.…”
Section: Discussionsupporting
confidence: 93%
“…The age of the donors included in our study ranged from 21-86 years. These observations are in agreement with data from other investigators, [21][22][23]34,35 who reported normal diploid karyotype without aneuploidy or polyploidy in MSCs from healthy donors or patients with no hematopoietic disorders.…”
Section: Discussionsupporting
confidence: 93%
“…The use of MSCs for therapeutic applications is based on their subsequent large-scale in vitro expansion, which may lead to genetic and epigenetic instabilities; however, up to now, data on MSC transformation are very few (Rubio et al,2005), showing normal karyotypes and DNA copy numbers in long-term culture (Rubio et al,2005;Zhang et al, 2007;. Telomeric deletions have been reported (Meza-Zepeda et al,2008), indicating that chromosomal aberrations may occur, but with a very low incidence .…”
Section: Methylation Changes During Bone Marrow Msc Culture: What Liementioning
confidence: 99%
“…To the best of our knowledge, there are no studies describing methylationsilencing mechanisms for Alk receptors in vitro, but epigenetic changes during ex vivo expansion (including methylation) have been described for mesenchymal stem cells (MSCs). Choi et al showed how MSCs from late passages increased their methylation state in genes related to DNA replication, cell cycle and adipogenic differentiation [26,27]. We can suggest that the changes occurring during expansion and prior to cell therapy applications may have special relevance for the final behavior of cells.…”
Section: Discussionmentioning
confidence: 81%